Infant vocalizing and phenotypic outcomes in autism: Evidence from the first 2 years. Issue 2 (28th October 2021) - Plate, Samantha; Yankowitz, Lisa; Resorla, Leslie; Swanson, Meghan R.; Meera, Shoba Sreenath; Estes, Annette; Marrus, Natasha; Cola, Meredith; Petrulla, Victoria; Faggen, Aubrey; Pandey, Juhi; Paterson, Sarah; et al.
Abstract: Infant vocalizations are early‐emerging communicative markers shown to be atypical in autism spectrum disorder (ASD), but few longitudinal, prospective studies exist. In this study, 23, 850 infant vocalizations from infants at low (LR)‐ and high (HR)‐risk for ASD (HR‐ASD = 23, female = 3; HR‐Neg = 35, female = 13; LR = 32, female = 10; 80% White; collected from 2007 to 2017 near Philadelphia) were analyzed at 6, 12, and 24 months. At 12 months, HR‐ASD infants produced fewer vocalizations than HR‐Neg infants. From 6 to 24 months, HR‐Neg infants demonstrated steeper vocalization growth compared to HR‐ASD and LR infants. Finally, among HR infants, vocalizing at 12 months was associated with language, social phenotype, and diagnosis at age 2. Infant vocalizing is an objective behavioral marker that could facilitate earlier detection of ASD.